Historical aspects of standard negation in Semitic - Sjörs, Ambjörn (Studies in Semitic languages and linguistics, 2017)
In Historical Aspects of Standard Negation in Semitic Ambjörn Sjörs investigates the grammar of standard negation in a wide selection of Semitic languages. The bulk of the investigation consists of a detailed analysis of negative constructions and is based on a first-hand examination of the examples in context. The main issues that are investigated in the book relate to the historical change of the expression of verbal negation in Semitic and the reconstruction of the genealogical relationship of negative constructions. It shows how negation is constantly renewed from the reanalysis of emphatic negative constructions, and how structural asymmetries between negative constructions and the corresponding affirmative constructions arise from the linguistically conservative nature of negative vis-à-vis affirmative clauses.